Difference-in-Difference Estimation by FE and OLS when there is Panel Non-Response - Michael Lechner; Núria Rodríguez-Planas; Daniel Fernández-Kranz (Institute for the Study of Labor (IZA), 2015)
We show that the OLS and fixed-effects (FE) estimators of the popular difference-in-differences model may deviate when there is time varying panel non-response. If such non-response does not affect the common-trend assumption, then OLS and FE are consistent, but OLS is more precise. However, if non-response is affecting the common-trend assumption, then FE estimation may still be consistent, while OLS will be inconsistent. We provide simulation as well as empirical evidence for this phenomenon to occur. We conclude that in case of unbalanced panels, deviating OLS and FE estimates should be considered as evidence that non-response is not ignorable for the differences-in-differences estimation.
Keywords: C21; C31; 330; difference-in-difference estimation; attrition; panel estimation; balanced panel; unbalanced panel